Biotransformation of wastewater production of bakery yeast with biogas generation - Bublienko, Natalia; Zaharova, Ruslana; Stetsenko, Natalia (My University, 2022)
Baker's yeast production plants are a source of environmental pollution with concentrated wastewater. They are usually diluted with water and discharged into sewerage networks. It is rational to use methane fermentation, which will ensure the removal of pollutants and make the process economically profitable through the use of biogas and digestate. Therefore, it is relevant to study the influence of fermentation parameters on the efficiency of purification. The purpose of the work is to study methane fermentation of yeast production wastewater in a continuous mode. Підприємства із виготовлення хлібопекарських дріжджів є джерелом забруднення довкілля концентрованими стічними водами. Зазвичай їх розводять водою і скидають у каналізаційні мережі. Раціональним є використання метанової ферментації, що забезпечить вилучення полютантів і зробить процес економічно вигідним через використання біогазу та дигестату. Тому актуальним є вивчення питання впливу параметрів ферментації на ефективність очищення. Мета роботи – дослідження метанової ферментації стоків дріжджових виробництв у безперервному режимі.
Keywords: кафедра екології та екоменеджменту; кафедра технології оздоровчих продуктів; biogas; vitamins; digestion; yeast production; methanogenesis; wastewater; біогаз; вітаміни; дигестат; дріжджове виробництво; метаногенез; стічні води